Perbedaan Terapi Guided Imagery Dan Aromaterapi Lemon Terhadap Nyeri Pada Ibu Post Section Caesarean - Dewi, Etika Rahmah; Aprilina, Happy Dwi (Jurnal Keperawatan Muhammadiyah, 2019)
THE DIFFERENCES BETWEEN GUIDED IMAGERY THERAPY AND LEMONAROMATHERAPY ON PAIN IN POST SECTION CESAREAN MOTHER1Etika rahmah dewi, 2Happy Dwi AprilinaABSTRACTÂ Background: Section caesarean is an act of surgery or an artificial labor whose purpose is to remove the baby by opening the mother's stomach and uterus with the incision of the mother's uterus intact. Section caesarean can cause unpleasant conditions because it makes the mother feel uncomfortable and afraid to mobilize and engage in activities. The use of pharmacological techniques to reduce pain can be combined with non-pharmacological techniques. A non-pharmacology technique that can be conducted is guided imagery therapy and lemon aromatherapy.Objective: Knowing the differences between guided imagery therapy and lemon aromatherapy therapy on Section Caesarean pain in respondents in RSUD Ajibarang after being given guided imagery therapy and lemonaromatherapy therapy.Method:A quantitative method with a quasi-experimental design with two group pretest-posttest with design was used in this study. The target of this study in post section caesarean women was divided into two groups. They were selected by purposive sampling technique. The pretest was taken in the form of initial measurements and posttest was in the form of final measurements after treatment by using Mann Whitney test.Result: The result showed that the difference between guided imagery therapy and lemon aromatherapy therapy which were given to 38 respondents for 1x24 hours for 10 minutes revealed that the intensity of the respondent pain scale decreased.Conclusion: After being given a nursing intervention about provision of lemon aromatherapy for respondents, it can be concluded that the provision of lemon aromatherapy is more effective to reduce pain scale than guided imagery therapy.